(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research was purposed 1. to develop the supervision model for enhancing learning management competency; and 2. to evaluate use of the supervision model for enhancing communicative English learning management competency of primary school teachers. The findings were found that 1. the supervision model for enhancing learning management competency consists of 1) principle; 2) objective; 3) the model/method which is directive informational supervision and collaborative coaching; 4) the supervision model process that is composed of fundamental information analysis, preparation, providing knowledge, supervision performance and reflection; 5) evaluation and 6) achievement indicators. The evaluation of the developed model gained suitability, feasibility and advantage at the highest level. 2. The evaluation of using the supervision model for enhancing communicative English learning management competency of primary school teachers revealed that 1) the evaluation of the supervision competency of supervisors was higher than before the development; 2) the supervisors’ satisfaction towards the supervision model for enhancing communicative English learning management competency of primary school teachers, in overall, was at the highest level; and 3) the teachers’ satisfaction towards the supervisors, in overall, was at the highest level as well.